2015
DOI: 10.1007/s12134-015-0447-8
|View full text |Cite
|
Sign up to set email alerts
|

Why Do So Many Children of Immigrants Attend University? Evidence for Canada

Abstract: The children of Canadian immigrants from some source regions, Asia, Africa and China in particular, attend university at extraordinarily high rates. Most others participate at lower rates, but still compare favourably with nonimmigrant Canadians. In this paper, the Youth in Transition Survey is used to analyse the role of various background factors on these outcomes, including parental education, family income, parental expectations, high school grades and PISA test scores. To some degree, the children of immi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…These results fit with earlier research by Foley, Gallipoli, and Green () and Childs, Finnie, and Mueller () for Canada. Both papers find that when parental aspirations are included, the effects of parental education and ethnic background on educational outcomes are reduced, and in the case of Foley et al ., the effect of parental education is completely eliminated…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These results fit with earlier research by Foley, Gallipoli, and Green () and Childs, Finnie, and Mueller () for Canada. Both papers find that when parental aspirations are included, the effects of parental education and ethnic background on educational outcomes are reduced, and in the case of Foley et al ., the effect of parental education is completely eliminated…”
Section: Resultssupporting
confidence: 92%
“…Earlier research suggests that the effect of parental education on university attendance may differ between the second and 3rd‐and‐higher generations. In Canada, the correlation between parents' education and the students' educational attainment is observed to be weaker among immigrant families than among domestic‐born families (Bonikowska, ; Childs, Finnie, and Mueller, ). Similar results are found in Switzerland (Bauer and Riphahn, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of this variable were expected to be mediated by the relationship between students' RIU attendance and their GPAs but previous research suggested language proficiency would also complement curricular achievement (Childs et al. ). The results indicate English language proficiency does play a significant role in predicting RIU attendance, independent of GPA scores (odds ratio of 1.02).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…). Although one might assume such language skills are incorporated in GPA measures, Childs, Finnie, and Mueller () found that PISA language scores had an effect independent of GPA in predicting students’ PSE participation. By extension, English language proficiency may be important in predicting admission to selective university programs.…”
Section: Introductionmentioning
confidence: 99%